Placental Cryptococcosis in an HIV Infected Woman with Eclampsia: A Rare Case Report - A, Shruthi; Jadhav, Meena N; Kittur, S K; Lakshmi, K S (Annals of Pathology and Laboratory Medicine, 2022)
Cryptococcosis is not uncommon, especially among immunocompromised patients. However, placental cryptococcosis is rare, with few reported cases in the literature. A 21 yr. old primigravida, a known case of HIV was admitted to hospital at 36 weeks gestation for antepartum hemorrhage. Her vital signs were within normal limits. Her laboratory investigations revealed hemoglobin-6 gm%. The peripheral smear showed microcytic hypochromic anemia. Urine showed traces of albumin. On the sixth day of admission, she developed features of eclampsia and delivered a male baby of birth weight 1700 gm. The placenta weighed 350 gm. Microscopy of placenta showed marked perivillous fibrin deposits, decidual arteriopathy and syncytial knots. At places, cryptococci were seen which showed thick capsule around them. A diagnosis of placental cryptococcosis with features of eclampsia was made. On the third day postpartum, she developed drowsiness and disorientation. CSF analysis was suggestive of cryptococcal meningitis. On the fifth day postpartum, patient died of DIC and multiorgan failure. It is important to establish the involvement of placenta by the opportunistic infections like Cryptococcus neoformans in immunocompromised women, so that the baby and the mother can be instituted with immediate appropriate management.